The relationship between job performance of selected MAR officers in Central Iloilo and the people's level of awareness about their functions - Villanueva, Quennie Marie
This research attempts to find out whether a relationship exists between the job performance of MAR Officers in Central Iloilo and the local people's level of awareness about their functions, especially those related to the legal services they offer. In the process of answering the said problem, the study study also aimed for the following: (1) to find out whether there are specified qualifications required of MAR Officers and if these are strictly followed by the DAR in hiring them; (2) to determine whether MAR Officers follow a common procedure in doing their functions, especially those related to the legal services they offer; (3) to examine the 1998 and 1999 work output of selected MAR Officers in Central Iloilo in order to determine their job performance; (4) to determine the level of awareness of the local people regarding the functions of the MAR Officers, especially those related to the legal services they offer; and (5) to determine the local people's assessment of the legal services offered by the MAR Officers to them. In as much as the researchers wanted to cover all the MAR Officers in Central Iloilo, constraints in time made them randomly select only two of the nineteen -- those of San Enrique and New Lucena. Farmer-respondents were also randomly selected from the largest rice producing barangay of the municipalities handled by the MAR Officers chosen to represent the local people.The data was obtained through one-on-one interviews with the respondents and was analyzed both qualitatively and quantitatively with the use of the correlation coefficient and the chi-square. The study revealed that indeed, a positive relationship exists between the two variables presented. It was also found out that the MAR Officers, as they are rigidly chosen and whose position is based on promotion, are very much capable of performing their assigned tasks and that there can be no overlapping of responsibilities with regards to the tasks performed by the MAR Officers and the other arms of the DAR system, although some of the tasks they perform can be done by fewer individuals. Moreover, the performance evaluation conducted by the PARO may not effectively monitor the MAR Officer's performance outside the identified aRCs and therefore, if possible, an evaluation of how the MAR Officers perform their limited tasks in non-ARCs should also be devised.